The Vatican in dialogue with Islam: inclusion and engagement - Pratt, Douglas (Islam and Christian-Muslim relations, 2010)
Since the epoch-making Second Vatican Council (1962–1965) the engagement of the Roman Catholic Church in interreligious dialogue and interfaith relations has developed and expanded. Other faiths, hitherto the object of missionary outreach for proselytising purposes, have been re-appraised as valued partners in dialogue. Islam, once regarded as the hostile ‘other’ to be held at bay, became, aside from Judaism, the first among the faiths with which the Church engages in dialogue. An overview of the origins and development of this dialogical activity during the twentieth century with special reference to the relation of the Vatican to Islam is the focus of this article. The topic is, of course, vast. The aim here is simply to distil the essential principles and processes, and to discuss some of the salient features. This dialogical development has not been without its difficulties; it remains, arguably, of critical concern.